2020
DOI: 10.1182/bloodadvances.2019001101
|View full text |Cite
|
Sign up to set email alerts
|

Genomic context and TP53 allele frequency define clinical outcomes in TP53-mutated myelodysplastic syndromes

Abstract: TP53 mutations are associated with adverse outcomes and shorter response to hypomethylating agents (HMAs) in myelodysplastic syndrome (MDS). Limited data have evaluated the impact of the type, number, and patterns of TP53 mutations in response outcomes and prognosis of MDS. We evaluated the clinicopathologic characteristics, outcomes, and response to therapy of 261 patients with MDS and TP53 mutations. Median age was 68 years (range, 18-80 years). A total of 217 patients (83%) had a complex karyotype. TP53 mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(102 citation statements)
references
References 34 publications
6
87
3
1
Order By: Relevance
“…In addition to TP53 mutations, TP53 VAF has also been reported to be of prognostic significance in MDS [17][18][19] . This is probably explained by the strong correlation between high VAF and biallelic targeting.…”
Section: Nature Medicinementioning
confidence: 99%
“…In addition to TP53 mutations, TP53 VAF has also been reported to be of prognostic significance in MDS [17][18][19] . This is probably explained by the strong correlation between high VAF and biallelic targeting.…”
Section: Nature Medicinementioning
confidence: 99%
“…62 studies were assessed full‐text articles for eligibility and 15 studies included qualitative synthesis, and 47 records were excluded for insufficient VAF data, no enough survival data, or other related articles. Finally, we include 11 articles 5,13‐22 covering 4003 cohort patients, 1138 TP53 mutant patients, and 1278 mutant TP53 sites. The selection process was documented in a flow chart recommended by the PRISMA (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Further validation is needed with a large sample study. In addition, some studies have shown that the mutation load of TET2 and TP53 has an effect on the overall survival time 24 26 . At present, few studies have reported that the mutation load of U2AF1 has an effect on the prognosis.…”
Section: Discussionmentioning
confidence: 99%